Enhancing Islamic Concepts through English Children’s Literature: Al- Ibtila, The Test of Patience - Yaroub, Ansam; Zuhair, Mayada; Abdul Sahib, Noor (Opción, 2019)
Allah, in his Holy Quran introduced great prophet stories so as to learn from. The greatness of these stories lies in Allah himself being the author. He portrays his characters, lays the plot, defines the tests and Al- Ibtilla, provides ways of being patient, using Duaa to end all hard tests and generously describing the greatness of his rewards to all those who are patient. The purpose of this research is to study selected English prophet stories for children on three levels, the stories ability to convey lessons and Islamic teachings to children who do not speak Arabic, the stories portray the Islamic concept of patience, the teaching and learning styles and strategies that Allah uses with each prophet. The concept of patience is defined as well as its meaning in different religions in general and in Islam in particular. Many types of patience are studied and applied on three prophets, Ayub (Job), Yunus (Jonah), and Musa (Moses) peace be upon them all to study the different types of tests, Ibtilla, suitable for individual differences among prophets, their response to the test, the type of patience need for them to pass the test, the Duaa they use to end the test and the type of reward they get for being patient. In addition to that, the researchers studied the teaching stratifies and styles Allah used with his prophets in connection with the most modern methods of teaching. The stories convey Islamic teachings, portrays the Islamic concept of patience and the individualized teach- ing style used with every prophet. The researchers conclude that Islamic children stories enhance Islamic concepts if they are introduced using up to date teaching strategies and styles.